PENGARUH PENERAPAN CHSE DAYA TARIK WISATA TERHADAP KEPERCAYAAN WISATAWAN YANG BERDAMPAK PADA MINAT BERKUNJUNG - Listyorini, Haniek; Hakim, Putra Arif Rahman (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
CHSE is a health protocol issued by the government to overcome the impact of COVID-19 on the economy, one of which is tourism. This study aims to examine whether there is an effect of the application of CHSE on tourist attraction and tourist trust, either partially or jointly, on visiting interest. The sample taken in this study were 210 respondents who live in Central Java. The data analysis method used in this study is quantitative with an inferential statistical approach and the data analysis technique used is multiple linear regression analysis. The results of the study show that tourist trust mediates the effect of applying CHSE at tourist attraction on Tourist visit interest.